2004
DOI: 10.1097/01.jom.0000105910.69449.b7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Work Performance and Physical Activity, Cardiorespiratory Fitness, and Obesity

Abstract: The purpose of this study was to test the association between lifestyle-related modifiable health risks (physical activity, cardiorespiratory fitness, and obesity) and work performance. Data were obtained from 683 workers. Dependent variables included number of work loss days, quantity and quality of work performed, overall job performance, extra effort exerted, and interpersonal relationships. Results indicated that higher levels of physical activity related to reduced decrements in quality of work performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
1
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 23 publications
6
174
1
11
Order By: Relevance
“…In addition, there may be relationships between obesity and other workplace issues, such as relations with co-workers (25). Some types of health behavior may also influence workplace costs and productivity or mediate the relationship between obesity and workplace costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there may be relationships between obesity and other workplace issues, such as relations with co-workers (25). Some types of health behavior may also influence workplace costs and productivity or mediate the relationship between obesity and workplace costs.…”
Section: Discussionmentioning
confidence: 99%
“…Bungum et al (9) categorized employees in the municipal workforce of an undisclosed city in the United States into the following three BMI groups: normal (BMI <25), overweight (BMI [25][26][27][28][29][30], and obese (BMI >30). Among those in the obese group, absenteeism was highest when compared with that of the normal weight and overweight groups.…”
Section: Workplace Impactsmentioning
confidence: 99%
“…Obesity is a major public health problem in the United States because of its high prevalence (Flegal et al, 2002), causal relationship with serious medical illnesses (Allison et al, 1999;Hu et al, 2001;Hubert et al,1983;Manson et al,1990), economic impact, and negative effects on work performance (Pronk et al, 2004). In 2003, the National Business Group on Health established The Institute on the Costs and Health Effects of Obesity, with a core objective being to "propose innovative solutions that large employers can implement to control costs related to lifestyle-related behaviors" (National Business Group on Health, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that improved functional capacity, as measured by cardiorespiratory fitness, is associated with improving of work productivity [11]. Even so, more knowledge is needed about activities that can prevent work ability and reduce sickness absence for workers with heavy physical work.…”
Section: Introductionmentioning
confidence: 99%